Hyperpresidentialism and fundamental rights in times of COVID-19. An analysis of the Paraguayan case (2020)
Over time, the typical separation of powers has essentially been maintained. However, non-minor changes such as the progressive development of rights, the responsibility of the State to guarantee them —reflected in the welfare state—, among other legal, social and political changes and conditions, have transcendently transformed the functioning, the accumulation of power and the designed balance of public power. Within this context, the Covid-19 pandemic did not transform this reality, but rather, intensified it exposing more clearly the progressive accumulation of power of the Executive Branch. The purpose of this paper is to expose the above mentioned and simultaneously to raise awareness in order to ensure a continuous and real balance of State powers. For these to function correctly and coordinately according to the mission theywere designed for: to protect and guarantee freedom, constitutional democracy, and fundamental rights.